Patients with Type 2 Diabetes: New Technologies and Social Media - Draughon, Ivonne (My University, 2015)
Patients with Type 2 Diabetes Mellitus (DMT2) often visit with primary care providers for quarterly checkups, as suggested by the American Diabetes Association (ADA) standards of care. Following these visits, which usually involve the creation of a provider-driven treatment plan, patients frequently fail to incorporate their providers’ directives into their existing routines and lifestyles. Patients often do not know how to make the daily changes necessary for living with diabetes. Social media and the internet have emerged as promising mechanisms for powerful, effective, and cost-conscious means of supporting patients in the self-management of diabetes. The purpose of this scholarly project is twofold. First, it is designed to analyze the gap in The American Diabetes Association’s 2014 guidelines for DMT2 patients related to the incorporation of technology in diabetic management. Second, this report is meant to develop a guideline on social media use for diabetic patients in primary care.
Keywords: Diabetes; Technology; Smart phones; Social media